2009
DOI: 10.2174/138920309788452218
|View full text |Cite
|
Sign up to set email alerts
|

The Classic Basic Protein of Myelin – Conserved Structural Motifs and the Dynamic Molecular Barcode Involved in Membrane Adhesion and Protein-Protein Interactions

Abstract: The myelin basic protein (MBP) family comprises a variety of developmentally-regulated members arising from different transcription start sites, differential splicing, and post-translational modifications. The "classic" isoforms of MBP include the 18.5 kDa form, which predominates in adult human myelin and facilitates compaction of the mature myelin sheath in the central nervous system, thereby maintaining its structural integrity. In addition to membrane-association, the 18.5 kDa and all other classic isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(136 citation statements)
references
References 183 publications
2
134
0
Order By: Relevance
“…The CNS myelin, although mostly composed of lipids, possesses many fundamental proteins which are essential for proper structural and functional integrity of the sheath (reviewed by [7]). Among these essential proteins are the myelin basic proteins (MBPs) [8][9][10][11][12][13], a family composed of developmentally regulated members arising from different transcription start sites of the Golli (Gene of Oligodendrocyte Lineage) complex, with further alternatively-spliced isoforms and combinatorial post-translational modifications [14]. 'Classic' MBP isoforms arise from transcription start site 3 and range in size from 14 kDa to the full-length 21.5-kDa transcript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNS myelin, although mostly composed of lipids, possesses many fundamental proteins which are essential for proper structural and functional integrity of the sheath (reviewed by [7]). Among these essential proteins are the myelin basic proteins (MBPs) [8][9][10][11][12][13], a family composed of developmentally regulated members arising from different transcription start sites of the Golli (Gene of Oligodendrocyte Lineage) complex, with further alternatively-spliced isoforms and combinatorial post-translational modifications [14]. 'Classic' MBP isoforms arise from transcription start site 3 and range in size from 14 kDa to the full-length 21.5-kDa transcript.…”
Section: Introductionmentioning
confidence: 99%
“…'Classic' MBP isoforms arise from transcription start site 3 and range in size from 14 kDa to the full-length 21.5-kDa transcript. They also undergo combinatorial post-translational modifications including phosphorylation and deimination of arginine, resulting in a number of charge components [11]. They adapt structurally and bind to a variety of different polyanionic proteins such as actin and tubulin, and also have been shown to have other important interactions with calmodulin and SH3-domain proteins such as Fyn kinase, the actin-polymerizing protein cortactin, and PSD-95 (presynaptic density protein 95) [8,[10][11][12][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the 21.5-kDa MBP isoform is intrinsically disordered like 18.5-kDa MBP, far less is known about its structural dynamics and possible self-association, and it is worthwhile to explore the effects of these mutations by NMR spectroscopy [14,15,44]. It has also been suggested that the phosphorylation status of several potential protein kinase C (PKC) phosphorylation sites within the N-terminal region of MBP may modulate their subcellular localization in OLGs [20,22,[31][32][33]45], another phenomenon worthy of further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Basic residues are colored blue and acidic residues are colored red. The amino acid numbering omits the Nterminal methionyl residue which is cleaved post-translationally, and follows our standard convention [15][16][17]. (B) ClustalW2 alignment of the conserved regions encoded by exon-II of 21.5-kDa MBP in various species.…”
Section: Cnsmentioning
confidence: 99%
See 1 more Smart Citation